Analysis of Educational Values in the Novel Suluh Rindu by Habiburrahman El Shirazy - Syahputra, Eko; Wiza, Rahmi (Journal of Multidisciplinary Science: MIKAILALSYS, 2023)
Moral education is an important aspect of Islamic education. However, what is happening now is the emergence of moral decline in the younger generation, making it important to apply the right educational strategy. One of the strategies that can be implemented to improve the problem of moral education is to utilize literary works in the form of novels. This study aims to examine the values of moral education contained in Habiburrahman El Shirazy's novel Suluh Miss. The method used is a qualitative method with a study of literature (library research). Data collection techniques using documentation techniques. From the research results, there are five moral attitudes towards oneself, namely humble attitude, istiqomah attitude, honest attitude, discipline attitude, and attitude of studying.